COVID‐19‐specific metabolic imprint yields insights into multiorgan system perturbations. Issue 3 (16th December 2021) - Cornillet, Martin; Strunz, Benedikt; Rooyackers, Olav; Ponzetta, Andrea; Chen, Puran; Muvva, Jagadeeswara Rao; Akber, Mira; Buggert, Marcus; Chambers, Benedict J.; Dzidic, Majda; Filipovic, Iva; Gorin, Jean‐Baptiste; et al.
Abstract: Corona disease 2019 (COVID‐19) affects multiple organ systems. Recent studies have indicated perturbations in the circulating metabolome linked to COVID‐19 severity. However, several questions pertain with respect to the metabolome in COVID‐19. We performed an in‐depth assessment of 1129 unique metabolites in 27 hospitalized COVID‐19 patients and integrated results with large‐scale proteomic and immunology data to capture multiorgan system perturbations. More than half of the detected metabolic alterations in COVID‐19 were driven by patient‐specific confounding factors ranging from comorbidities to xenobiotic substances. Systematically adjusting for this, a COVID‐19‐specific metabolic imprint was defined which, over time, underwent a switch in response to severe acute respiratory syndrome coronavirus‐2 seroconversion. Integration of the COVID‐19 metabolome with clinical, cellular, molecular, and immunological severity scales further revealed a network of metabolic trajectories aligned with multiple pathways for immune activation, and organ damage including neurological inflammation and damage. Altogether, this resource refines our understanding of the multiorgan system perturbations in severe COVID‐19 patients. Abstract : Through in‐depth metabolomics analysis combined with clinical metadata, we first define a COVID‐19‐specific metabolic imprint. By integrating this with large‐scale proteomic and flow cytometry data, metabolic trajectories associated with immune activation and organ damage are identified. This resource illustrates ongoing multisystem perturbations in severe COVID‐19 patients.